Differentiation of mouse myeloid leukemia cells induced by 1 alpha,25-dihydroxyvitamin D3. - Abe, E (1981)
Mouse myeloid leukemia cells can be induced to differentiate into macrophages in vitro by 1 alpha,25-dihydroxyvitamin D3, the active form of vitamin D3. The minimal concentration of 1 alpha,25-dihydroxyvitamin D3 to induce the cell differentiation was 0.12 nM. The degree of cell differentiation in various markers induced by 12 nM 1 alpha,25-dihydroxyvitamin D3 was nearly equivalent to that induced by 1 microM dexamethasone, the most potent known stimulator. Among several markers of the differentiation by 1 alpha,25-dihydroxyvitamin D3, phagocytic activity was induced within 24 hr, and this was followed by induction of lysozyme and locomotive activities. Similar changes were also induced by 0.01-1 microM 1 alpha-hydroxyvitamin D3. 25-Hydroxyvitamin D3 and 24R,25-dihydroxyvitamin D3 showed only weak inducing activity. These results suggest the possibility that, in addition to its wellknown biological activities in enhancing intestinal calcium transport and bone mineral mobilization, 1 alpha, 25-dihydroxyvitamin D3 is involved in the differentiation of bone marrow cells.